Improvement of freight transport technologies and implementation of new technologies - Baublys, Adolfas (Transport, 2003)
The synthesis of regional (urban) road transport freight system topological structure enables the assessment of impact exercised by various structural characteristics on the functioning of the system. For this reason the quality of project solutions in the stage of system structural synthesis increases. Models of optimisation and simulation (included into the simulation procedure of optimisation of topological structure) have other possibilities as well. For instance, simulation model enables the solution of such various objectives of functional analysis of systems as, for example, the efficiency comparison analysis of stability of structure undergoing the changes of meanings of system parameters, the analysis of managing impacts of various types, loading technologies, etc.First Published Online: 19 Dec 2011